The ex hex [compact disc, unabridged] - Sterling, Erin (Harper Audio, 2021)
Nine years ago, Vivienne Jones nursed her broken heart like any young witch would: vodka, weepy music, bubble baths, and a curse on the horrible boyfriend. Sure, Vivi knows she shouldn't use her magic this way, but with only an 'orchard hayride' scented candle on hand, she isn't worried it will cause him anything more than a bad hair day or two. That is until Rhys Penhallow, descendent of the town's ancestors, breaker of hearts, and annoyingly just as gorgeous as he always was, returns to Graves Glen, Georgia. What should be a quick trip to recharge the town's ley lines and make an appearance at the annual fall festival turns disastrously wrong. With one calamity after another striking Rhys, Vivi realizes her silly little Ex Hex may not have been so harmless after all.